(untitled) (Педагогіка вищої та середньої школи, 2006)
In the given article the history of the dialogue foundation, ilvvclopment of the dialogue interaction skills are considered. The iiuthor of the article emphasizes the necessity of the formation of the students’ skills to conduct a dialogue, many of which were already determined by mined by the philosophers of antiquity and middle ages.